Icarus digital image processing and classification of remotely-sensed data images - Cabral, Fiel Sixto; Castro, Arnold; Gonzales, Ma. Yda Mitzy; Yenko, Marivic; Yupangco, Alfie (1996)
Remote sensing is the acquisition of information on an object or phenomenon, by a device that is not in physical contact with the object under study. Information such as measurements of force fields, electromagnetic radiation, and acoustic energy are obtained using devices such as cameras, lasers, radio receivers, radar and sonar which are attached to aircraft, spacecraft, or ships. Remotely sensed image data may be procured either in photographic form or as digital data on magnetic tape. Computers are needed to analyze remotely sensed images. First an image is converted into digital form and then fed into the computer. The computer can then analyze the digitized image using image processing algorithms. These algorithms can darken lines in the image, sharpen contrast, diminish detail or classify points based on the type of vegetation or land cover that they contain. Originally, remote sensing was used for map-making and military reconnaissance. However, it has been used for other applications such as monitoring the changing levels of lakes and reservoirs, assessing crop diseases, locating new highway routes, assessing real estate and mapping archeological sites. Remote sensing is a valuable tool for researchers and scientists in the Philippines. The distances separating our many islands make travel difficult and time consuming. Remote sensing allows experts to study distant or dangerous areas with relative ease. Since our people's main source of livelihood is still agriculture, remote sensing can also aid in locating mineral deposits. Here are some government agencies which use remote sensing: NAMRIA, National Mapping and Resource Information Authority -- They make topographical maps as well as maps of cities. In the latter, roads are difficult to distinguish from the image so image enhancement is used to define them. Image classification yields land use maps. DENR, Department of Environment and Natural Resources -- Scanned images are used for monitoring forest cover as well as gauging the rate of deforestation. Philippine Council for Health, Research and Developmemt -- They use real time satellite feed (GMS and NOAH) to monitor the climate as well as other weather events such as floods. PHIVOLCS, Philippine Institute of Volcanology and Seismology -- They use scanned images to create geologic maps as well as monitor lahar flows and alluvial and puroclastic deposits near Mt. Pinatubo. Bureau of Soils and Water Management -- Scanned images are used to classify soil in an area into certain types. In agriculture research, remotely sensed data are used to monitor the stages of the growth of rice crops (i.e. ready to harvest or just starting to grow). Although there are potentially many applications of remote sensing in the Philippines and there are sources of digitized satellite images, the high cost of image processing hardware and software prevents more groups from venturing into this field. There are also few image processing software packages which are specially written for remotely sensed images. Thus our goal is to produce a Windows-based image processing program which enhances and classifies remotely sensed images. We chose the Windows platform because many offices now have computers that are capable of running Windows. These computers are much less expensive than the advanced workstations typically required to do image processing. We also chose Windows because it offers a friendly and consistent user interface. It also gives our software more control over the computer's memory and video hardware. Moreover, with our software running under Windows users can transfer iamges from our software to other programs for conversion to other file formats or for printing, for instance. It is our hope that this project will encourage more Filipino experts to enter into remote sensing applications and that more Filipino programmers will write software specifically for remote sensing.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Image processing -- Digital techniques; Remote sensing -- Data processing